Measuring efficiency of intellectual capital in agriculture sector of Vojvodina - Komnenic, Biserka; Tomic, Danilo; Tomic, Gordana (Applied Studies in Agribusiness and Commerce, 2010)
During three-hundred-year history of the market economy, the main sources of wealth creation have changed from the natural resources (mainly land and relatively unskilled labor with the exception of the master craftsman), tangible material assets (buildings, machinery and equipment, funds) to intangible assets (knowledge and information of all types) that may be contained in the people, organizations, or physical resources. In the later period of the twentieth century, science has acquired the features of direct production force. The term direct implies that unlike the relationship which existed between science and production in the IXX century, where scientific advances was incorporated through the physical labor in the tools, which, in turn, created new value through the physical labor, the relationship between science and production has become all direct, immediate, because the scientific advances allowed the funds to be produced with less labor and allowed funds itself to become "smarter" and as such to require less human intervention and human physical labor in the final production process.As a result, the need for physical labor continuously declined with time, and the application of labor is moved from direct production to processes of preparing and organizing production. Also, a large part of today’s knowledge that is used in production is not embodied in machinery, and the effects of this are immense.